Rent control reduces economic inequality at a price - Konstantin Kholodilin; Sebastian Kohl (DIW Weekly Report, 2022)
Over the course of the 20th century, governments have frequently used rent control to keep rents affordable, especially in times of crisis when housing is scarce. Existing research shows that rent control has undesirable side effects, such as overall societal welfare losses, market misallocation, a declining housing supply, and lower mobility. However, there has been little research examining the effect of rent control on economic inequality. Income inequality has been rising worldwide since the 1980s. While previous explanations of this development focused on the relationship between the growth of capital and wages and social policy measures, this paper argues a housing dimension should be considered as well. Using a time series analysis, we investigate what impact rent control has on income inequality. The analysis shows that rent control significantly reduces the social inequality as measured by the Gini index and reduces the wealth-to-income ratio. The stricter the measures taken, the stronger the effects. Existing data suggest that lower income groups spend a larger share of their income on rent, while rental income makes up a large share of the income of higher income groups. When rent-reducing measures are taken, the disposable income of the lower-income groups will rise and the income share of the top ten percent will decrease in the short run. Policymakers must decide how to weigh the effects and the impact of rent control on overall social welfare and the rental housing market.
Keywords: C32; E27; E32; 330; Competition and Regulation; Distribution; Inequality; Markets; Real estate and housing